DARI DESENTRALISASI HINGGA GOOD GOVERNANCE: ANTARA HARAPAN DAN REALITAS - Abd Mu’id Aris Shofa (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: The decentralization in Indonesia has existed since colonial era with the enactment oflegislation ‘desentralizatie wet’ in 1903. Decentralization was expected to deliver good governance inIndonesia government system. But even reformation has been running nearly 16 years, problemssuch as corruption, mal-administration, and abuse of power still exist in Indonesia government.These problems can be solved with stategic manner, such as preparation of the legal framework ofbureaucratic management by making changes to employment laws, bureaucracy should be managedprofessionally and separate with political party, positioning adapted to the each potential employeeor technical capabilities, there should be prohibition against the politicization of the bureaucracy bypolitical authorities both at central and regional levels, and the last one there must be political willfrom the government or society.